Role of intraoperative PTH monitoring and surgical approach in primary hyperparathyroidism. Issue 3 (September 2015) - Khan, Angela A.; Khatun, Yasmin; Walker, Abigail; Jimeno, Jaime; Hubbard, Johnathan G.
Abstract: Aims: The use of intraoperative PTH monitoring (IOPTH) in combination with preoperative imaging has been useful to surgeons performing minimally invasive parathyroidectomy principally for adequacy of excision. However, its role within patients with equivocal imaging remains less clear particularly regarding the reduction of bilateral neck explorations. This study investigated the influence of IOPTH monitoring on the type of surgical approach adopted for patients with primary hyperparathyroidism (PHPT). Specifically, determining its impact amongst patients with equivocal imaging results. Methods: 165 patients undergoing parathyroidectomy for PHPT at a single institution by a single surgeon, between 2008 and 2012, were included. Patients were divided into 2 groups, IOPTH monitoring and non-IOPTH monitoring. They were sub-classified according to their imaging strengths: strongly positive, equivocal and negative imaging. The percentages of patients undergoing focused, unilateral and bilateral operations were determined. Results: 108 patients had IOPTH monitoring and 57 patients did not based on the availability of IOPTH monitoring. Patients with strongly positive imaging had a higher frequency of focused operation in both groups; IOPTH 73.4% and non-IOPTH 71.4%. Patients with negative imaging results had a higher frequency of bilateral operations; IOPTH 77.8% and non-IOPTH 72.7%. In patients with equivocal imaging results more focused/unilateral operations were performed with IOPTH monitoring 66.6% versus non-IOPTH 25%. The use of intraoperative PTH increased the likelihood of a unilateral procedure with equivocal imaging compared to those with negative imaging p = 0.04. Conclusion: IOPTH monitoring is most useful as an adjunct to preoperative imaging when imaging results are equivocal allowing for more focused/unilateral operations to be performed. Highlights: IOPTH monitoring confirmed cure during surgery. It influenced the surgical approach taken in those with equivocal imaging results. This determined extent of surgical treatment required to be considered optimum.